Building product populations with software components - van Ommering, Rob (Proceedings - International Conference on Software Engineering, 2002)
Two trends have made reuse of embedded software for consumer electronics an urgent issue: the software of individual products becomes more and more complex, and the market demands a larger variety of products at an increasing rate. For that reason, various business groups within Philips organize their products as product families. A third trend is the integration of functions that until now were only found in separate products (e.g. a TV with Dolby Digital sound and a built-in DVD player). This requires software reuse between product families, which - when organized systematically - leads to a product population approach.We have set up such a product population approach, and applied it in various business groups within our organization. We use a component technology that stimulates context independence, and allows the composition of new products out of existing parts. We use an architectural description language to explicitly describe the architecture, and also to generate efficient bindings. We have aligned our development process and organization with the new 'compositional' way of working. This paper outlines our approach and reports on our experiences with it.